From biomarkers to therapeutics : diagnostic signatures and novel strategies targeting GPCRs in Parkinson's disease - Andrea Sturchio (2026)
Parkinson's disease is the second most common neurodegenerative disorder and is characterized by a wide range of symptoms, including both motor and non-motor features. Despite extensive research, robust biomarkers are still lacking, and the underlying pathophysiology remains unclear. Consequently, a disease-modifying therapy for Parkinson's disease is still unavailable. The aim of this thesis is to investigate specific Parkinson's disease biomarkers and identify potential therapies targeting G-protein-coupled receptors, including their role in the pathophysiology of the disease.One advantage in Parkinson's disease research is that several risk factors are already known. One of the most prominent is the GBA1 mutation, which affects a gene encoding the lysosomal enzyme glucocerebrosidase. Glucocerebrosidase is involved in glycosphingolipid metabolism by acting on its substrate, glucosylceramide. When the GBA1 mutation is present, glucocerebrosidase dysfunction leads to glucosylceramide accumulation, resulting in cellular dysfunction. In paper I, we investigated glycosphingolipid metabolism and found that the alterations are broader than previously expected. Interestingly, these changes were also present in Parkinson's disease subjects without the GBA1 mutation and were not limited to glucosylceramide, providing new insights into how glucocerebrosidase could affect Parkinson's disease.This thesis also explored the role of a recently proposed Parkinson's disease biomarker, DOPA decarboxylase. In papers II, III, and IV, we examined multiple aspects of DOPA decarboxylase. We found that DOPA decarboxylase levels are increased not only in Parkinson's disease subjects under treatment but also in de novo and prodromal Parkinson's disease cases. This finding is crucial for more effective patient stratification in clinical trials. Additionally, DOPA decarboxylase proved to be a valuable biomarker not only for diagnosis but also for disease progression, as higher DOPA decarboxylase levels were associated with greater dopaminergic degeneration and more severe cognitive decline.In paper V, we targeted a specific G-protein-coupled receptor to develop new therapeutic molecules. Using Artificial Intelligence, we identified small molecules that target Trace Amine-Associated Receptor 1, a promising receptor for addressing psychotic symptoms in Parkinson's disease.Finally, paper VI uncovered a novel biological function of alpha-synuclein, a key protein in Parkinson's disease pathogenesis. We demonstrated that alpha- synuclein interacts with GPR109A, a receptor expressed in microglia that regulates various inflammatory processes. This discovery provides new insights into the disease's underlying mechanisms and may open avenues for future therapeutic strategies.List of scientific papersI. * Te Vruchte D, *Sturchio A, Priestman DA, Tsitsi P, Hertz E, Andréasson M, Markaki I, Wallom KL, Platt F, Svenningsson P. Glycosphingolipid Changes in Plasma in Parkinson's Disease Independent of Glucosylceramide Levels. Mov Disord. 2022 Oct;37(10):2129-2134. https://doi.org/10.1002/mds.29163II. Appleton E, Khosousi S, Ta M, Nalls M, Singleton AB, Sturchio A, Markaki I, Paslawski W, Iwaki H, Svenningsson P. DOPA- decarboxylase is elevated in CSF, but not plasma, in prodromal and de novo Parkinson's disease. Transl Neurodegener. 2024 Jun 11;13(1):31. https://doi.org/10.1186/s40035-024-00421-0III. * Khosousi S, *Sturchio A, Appleton E, Paslawski W, Ta M, Nalls M, Singleton AB, Iwaki H, Svenningsson P. Increased CSF DOPA Decarboxylase Correlates with Lower DaT-SPECT Binding: Analyses in Biopark and PPMI Cohorts. Mov Disord. 2024 Oct;39(10):1881- 1885. https://doi.org/10.1002/mds.29835IV. * Sturchio A, *Paslawski W, Khosousi S, Markaki I, Nalls MA, Singleton AB, Iwaki H, Svenningsson P. High Cerebrospinal DOPA Decarboxylase Level Predicts Cognitive Decline in Parkinson's Disease. Mov Disord Clin Pract. 2025 Sep 24. https://doi.org/10.1002/mdc3.70367V. Díaz-Holguín A, Saarinen M, Vo DD, Sturchio A, Branzell N, Cabeza de Vaca I, Hu H, Mitjavila-Domènech N, Lindqvist A, Baranczewski P, Millan MJ, Yang Y, Carlsson J, Svenningsson P. AlphaFold accelerated discovery of psychotropic agonists targeting the trace amine-associated receptor 1. Sci Adv. 2024 Aug 9;10(32):eadn1524. https://doi.org/10.1126/sciadv.adn1524VI. #Sturchio A; Saarinen M; Camargo A; Yang Y; #Svenningsson P. Monomeric alpha-synuclein activates GPR109A. [Manuscript]*Equal contribution #Corresponding author